HUBUNGAN ANTARA KEPRIBADIAN INTROVERT DENGAN MOTIVASI BELAJAR SISWA KELAS VIII DI SMP NEGERI 8 KEDIRI - Mulyah, Ambar Tutut; Khususiyah, Khususiyah; Gumilang, Galang Surya (Universitas Nusantara PGRI Kediri, 2018)
Introverted personality is the condition of individuals who have a closed tendency, both the nature and the behavior that is more like to be alone, likes silence, individuality, and trying to pull away from the environment. Students who have introverted personality have a relationship with their learning motivation in school so that will affect their learning achievement. The purpose of this research is to obtain information and get accurate data about introvert personality relationship with the motivation of studying class VIII students in SMP Negeri 8 Kediri Academic Year 2016/2017. This research uses correlational technique with quantitative approach. The process of data analysis using Product Moment Correlation and the sample in this study are 70 students of class VIII SMP Negeri 8 Kediri. The data collection uses an introverted personality questionnaire instrument and learning motivation. The result of data analysis using Product Moment Correlation test shows positive relationship between Introvert Personality with Motivation Learning relationship between introvert personality with student learning motivation is shown with value of r count 0,502 bigger than r table 0,235 with significance level 5% (0,502 ≥ 0,235). Because the correlation value is in the range of 0.40 - 0.599, it is concluded that the relationship between variables X with variable Y is moderate. Then it can be concluded that Ho is rejected and Ha accepted, reads a relationship between introvert personality with the motivation of studying class VIII students in SMP Negeri 8 Kediri Academic Year 2016/2017. Based on the results of research that has been done suggestions that need to be raised is to be by teachers guidance and counseling can be used as a source of materials to improve the quality of science guidance and counseling.